Cucumber CsTRY Negatively Regulates Anthocyanin Biosynthesis and Trichome Formation When Expressed in Tobacco - Zhang, Leyu; Pan, Jian; Wang, Gang; Du, Hui; He, Huanle; Pan, Junsong; Cai, Run (Frontiers in Plant Science, 2019)
The development of trichomes(spines) on cucumber fruits is an important agronomic trait. It has been reported that two MYB family members, CsMYB6 and CsTRY act as negative regulators of trichome or fruit spine initiation. To further study the functions of these two genes, we overexpressed them in tobacco, and found that the flowers and seed coats of transformants overexpressing CsTRY displayed an unexpected defect in pigmentation that was not observed in plants overexpressing CsMYB6. Morever, the expression of key genes in the flavonoid synthesis pathway was repressed in CsTRY overexpressing plants, which resulted in the decrease of several important flavonoid secondary metabolites. In addition, CsTRY could interact with the AN1 homologous gene CsAN1(GY14 Cucsa.135510) in cucumber, which further confirmed that CsTRY not only regulates the development of fruit spines, but also functions in the synthesis of flavonoids, acting as the repressor of anthocyanin synthesis.